The effects of sodium citrate ingestion on metabolism and 1500-m-racing in trained female runners - Ööpik, V.; Timpmann, S.; Kadak, K.; Medijainen, L.; Karelson, K. (Journal of Sports Science & Medicine, 2008)
The purpose of the study was to assess the effects of sodium citrate ingestion on the metabolic response to exercise and performance in a 1500-m competitive run in trained female middle-distance runners in field conditions. Seventeen athletes (mean (± SD) aged 18.6 ± 2.5 years, VO2max 55.2 ± 7.6 ml·kg-1·min-1) competed in two 1500-m races following ingestion of 0.4 g·kg-1 body mass of sodium citrate (CIT) and placebo (PLC - 1.0% solution of NaCl). The two substances, CIT and PLC were administered in 800 ml of solution in a randomly assigned double-blind crossover manner. Capillary blood samples were analysed for lactate, glucose, haemoglobin and haematocrit before administering the solutions (baseline) as well as before and after both 1500-m races. The athletes' times for trials CIT and PLC were 321.4 ± 26.4 and 317.4 ± 22.5 s, respectively (p > 0.05). A greater relative increase in plasma volume after administering the experimental solution, an increased body mass (by 0.4 kg; p = 0.006) immediately before the race and a restrained increase in blood glucose concentration (by 2.5 ± 1.2 mmol·l-1 vs 3.4 ± 0.8 mmol·l-1; p = 0.002) during the race were observed in the CIT trial compared to the PLC. A significant relationship was observed between body mass of the subjects immediately before the race and performance time (r = 0.374; p = 0.029). There were no between-treatment differences in heart rate in any stage of the run or in blood lactate accumulation during the race (final concentration of lactate was 14.4 ± 3.0 mmol·l-1 and 13.4 ± 2.5 mmol·l-1 (p > 0.05) in the CIT and PLC trials, respectively). The results suggest that sodium citrate induces an increase in water retention before exercise and may modify carbohydrate metabolism in high intensity running, but does not improve performance in 1500-m competitive run in female middle-distance runners.